India: thank you, climate change? - International Center for Tropical Agriculture (2012)
In Himachal Pradesh, northern India, rising temperatures over the past few decades have shifted high-value apple production to higher, cooler ground. But instead of losing a vital source of income, former apple farmers downhill have switched to the production of highly profitable vegetables, supplying domestic markets far and wide. In fact, they're now making even more money then when they grew apples. Farmers uphill who now grow apples are enjoying the benefits of switching from subsistence crops, with significant improvements in living standards. This short film shows that while climate change poses substantial threats to the livelihoods of small farmers, successful adaptation is possible, and that climate change - if managed properly - could be a blessing in disguise.